Departure points: beginning training in sited-based performance practices. Issue 2 (4th May 2018) - Quigley, Karen
Abstract : This article presents analysis drawn from my research project, 'Teaching On Site'. This project explores training methodologies for sited, interactive and/or immersive practices in universities in the UK. Using interviews with practitioners and scholars in this field as an investigative research methodology, the article analyses the multiplicity of approaches to teaching this slippery, outdoors, public subject. Scholars and practitioners of these performance practices rarely write about their teaching in this area, which has the effect of creating a closed set of pedagogies that become tied to a particular person. I am interested in developing a national and international conversation about ways of teaching site-based practices, and investigating trends and frictions, as well as the implications of these for trainee practitioners, in this case undergraduate students. This article's analysis focuses on starting points for student training in this area. From an emphasis on architecture and landscape, to an invitation to improvise with incidental audiences in public space, from historical research into a site and its users, to an offering of private stories from the trainees' pasts: departure points proposed to those in training engage a range of performative modes, and identify a variety of complex needs as training progresses.